Saint Guadalupe, Save Me and Protect Me: Tattoos on Life and Death (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
In the current article, I will share some of my narrative fragments and the history of two tattoos that I made during my fieldwork season in Mexico through the years 2012 and 2017. What I mean to explain here, is the reflection about my corporal construction around the tattoo and how the ethnographic experience brought considerable changes in my being. Is my search to open the discussion and the reflection about our investigative practice which often we set aside or give it not enough epistemological importance. Thereby, I close the writing proposing some questioning as an invitation on re-thinking how we knowledge co-construct with and of the others knowledge, how we knowledge co-construct whit others people bodies and whit our ones, how we can express and communicate the not understandable from our sense frame, whit our emotional conception and practices; What happens on that “me”, as the fieldwork season get to the end and we go back to the origin place, to the previous “normality”.
Keywords: Tattooing; autoethnography; body; health and illness